2005
DOI: 10.1177/153537020523000304
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Exercise Training Programs on Cardiac Responsiveness to β-Stimulation in Obesity

Abstract: We demonstrated previously that exercise training did not restore normal cardiac beta-adrenergic responsiveness in obese rabbits. This study tested the hypothesis that an increased training volume was required to attenuate obesity-related reductions in isolated heart responsiveness to isoproterenol. Female New Zealand White rabbits were divided into lean control, lean exercise-trained, obese control, and obese exercise-trained groups. For the exercise-trained groups, total treadmill work over 12 weeks was incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…As for obese rabbits [19], we hypothesized that intense exercise training in diabetic rats might decrease myocardial responsiveness to β-adrenergic stimulation. Consistent with an earlier study [3], we found that diabetes induces a rightward shift in the isoproterenol dose-response relationships without altering the magnitude of the peak responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for obese rabbits [19], we hypothesized that intense exercise training in diabetic rats might decrease myocardial responsiveness to β-adrenergic stimulation. Consistent with an earlier study [3], we found that diabetes induces a rightward shift in the isoproterenol dose-response relationships without altering the magnitude of the peak responses.…”
Section: Discussionmentioning
confidence: 99%
“…Intense exercise training during diabetes decreases cardiac β2-adrenoceptors expression. Thus, based on these data and others in different experimental models (healthy rats, obese rabbits...), we hypothesized that exercise training may affect differently all of the above mentioned factors depending on the load [ 18 , 19 ]. The present study was conducted to investigate the effect of 8 weeks of intense exercise training on both cardiac function and β-adrenergic system in diabetic rat hearts.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have documented studies in which feeding rabbits a high-fat diet, for periods ranging from 2-12 weeks, results in increased adiposity, associated with a 10-20% increase in mean arterial pressure (MAP) and a 10-35% increase in HR. 2,[6][7][8][9][10][11][12][13][14][15][16] Telemetric recordings in the fat-fed rabbit have shown that elevations in MAP and HR occur quickly, within days of commencing fat feeding, even before major changes in body weight occur. 9,17 Furthermore, increases in MAP and HR are progressive, within a 3-week time frame, but then seem to plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Because sympathetic activity is a major determinant of arrhythmia susceptibility, investigators have examined the effect of exercise training on the ␤-ARs using radioligand binding or protein level measurements. These measurements could not demonstrate a change in ␤-receptor expression following exercise training (3,12,16,37). While differences between the studies could result from protocol duration and intensity, none of these studies found a change in the ␤-receptor affinity.…”
Section: Discussionmentioning
confidence: 61%
“…Because the training protocol was adjusted according to the running speed of KO mice, the exercise intensity (at most 15 m/min) was rather mild for normal animals. Apparently, exercise adaptation was less pronounced in healthy animals due to inadequate training volume (3,15).…”
Section: Discussionmentioning
confidence: 98%